Clinical Characteristics of Hyperandrogenism Include Hirsutism, Polycystic Ovary Syndrome, and Acne: Association with Psychiatric Disease in Women -A Nationwide Population-Based Cohort Study in Taiwan - Wang TM; Chou CH; Lee YL; Chung CH; Huang YC; Lai XC; Sun CA; Kang CY; Wu GJ; Chien WC (International Journal of Women's Health, 2022)
Tsan-Min Wang,1,2 Cheng-Hao Chou,1,2 Yi-Liang Lee,3,4 Chi-Hsiang Chung,1,5,6 Yao-Ching Huang,1,7 Xiao-Cheng Lai,8 Chien-An Sun,9,10 Chieh-Yi Kang,11 Gwo-Jang Wu,1,3,12 Wu-Chien Chien1,5,6,8 1Department of Medical Research, Tri-Service General Hospital, Taipei, Taiwan; 2Taipei Municipal Jianguo High School, Taipei, Taiwan; 3Department of Obstetrics and Gynecology, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, Republic of China; 4Department of Obstetrics and Gynecology, Kang Ning Hospital, Taipei, Taiwan, Republic of China; 5School of Public Health, National Defense Medical Center, Taipei, Taiwan; 6Taiwanese Injury Prevention and Safety Promotion Association (TIPSPA), Taipei, Taiwan; 7Department of Chemical Engineering and Biotechnology, National Taipei University of Technology (Taipei Tech), Taipei, Taiwan; 8Graduate Institute of Life Sciences, National Defense Medical Center, Taipei, Taiwan; 9Department of Public Health, College of Medicine, Fu-Jen Catholic University, New Taipei City, Taiwan, Republic of China; 10Big Data Research Center, College of Medicine, Fu-Jen Catholic University, New Taipei City, Taiwan, Republic of China; 11Chi Mei Medical Center Gynecologic Oncologist Division, Department of Obstetrics & Gynecology, Tainan City, Taiwan, Republic of China; 12Graduate Institute of Medical Sciences, National Defense Medical Center, Taipei, TaiwanCorrespondence: Gwo-Jang Wu; Chieh-Yi Kang, Email gwojang@yahoo.com; albert0113@yahoo.com.twObjective: Previous studies have shown an increased in psychiatric disorders in women with disorders associated with hyperandrogenism, but few nationwide cohorts have studied this phenomenon. Therefore, this study is aimed to examine the association between the clinical manifestations of hyperandrogenism and subsequent psychiatric disorders.Methods: Based on the National Health Insurance Research Database, 49,770 enrolled participants were matched for age and index date between January 1, 2000, and December 31, 2015. Hirsutism, polycystic ovary syndrome, and acne are characterized by hyperandrogenism. After adjusting for confounding factors, we used Cox proportional analysis to compare the risk of psychiatric disorders during the 16 years of follow-up.Results: Of all the participants, 1319 (13.25%) had psychiatric disorders in the study group, whereas only 3900(9.80%) had psychiatric disorders in the control group. After adjusting for age, and monthly income, the Cox regression analysis showed that the study patients were more likely to develop psychiatric disorders (hazard ratio [HR]: 2.004, 95% confidence interval [CI] = 1.327– 2.724, P < 0.001). The results demonstrated that women aged 20– 29 years had a more significant risk.Conclusion: Women with clinical characteristics of hyperandrogenism have a higher risk of developing psychiatric disorders, especially those aged 20– 29 years.Keywords: hyperandrogenism, psychiatric disorders, national health insurance research database, cohort study, women, Taiwan